(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the application of Bloom’s Taxonomy in teaching English listening skills to EFL learners, emphasizing a cognitive approach to enhance both comprehension and critical thinking abilities. Bloom’s six cognitive levels—Remembering, Understanding, Applying, Analyzing, Evaluating, and Creating—offer a structured framework for designing listening tasks that cater to diverse learning needs. By progressing from basic recall of information to the creation of new responses based on auditory input, students engage in a more dynamic learning process that transcends rote memorization. The integration of Bloom’s Taxonomy into listening instruction allows educators to scaffold listening activities that gradually build higher-order thinking skills, such as analyzing speaker intent, evaluating arguments, and creating original content. This approach not only strengthens students’ listening proficiency but also promotes cognitive development by encouraging deeper engagement with the material. Through a combination of theoretical exploration and practical examples, this article demonstrates how adopting Bloom’s Taxonomy can transform English listening instruction for EFL learners, fostering a more comprehensive and critical engagement with language learning.